Celestial Bodies : A Collection of Poems - Palko, Meghan (East Carolina University, 2012)
A celestial body, according to Merriam-Webster, is "an aggregation of matter in the universe that constitutes a unit for astronomical study." More specifically, it is a planet, nebula, star, or some such natural heavenly entity. "Celestial Bodies" is a collection of poems dealing with these bodies. The human body and its celestial nature is a recurring aspect of my constellation of poems, whether literal or figurative. It is composed of mostly lyric poems from a first- or second-person point of view. Though actual astronomical fixtures and images appear throughout many of the poems, they only function as parentheses to the larger context of each poem. Many of them are influenced by natural setting, though the emotion or pursuit within the poem itself exists in a larger context. Lyric poetry, which originated in Greece around the 7th century B.C., was championed by Sappho and was originally intended for accompaniment on the lyre. As an aristocrat and scholar of poetry, Sappho wrote emotional, I-centered poems about the speaker's personal, often-erotic reflections and desires, which was contrary to predominant poetic trends of the time, such as Homer's long-winded epics. Since then many poets have slid easily into lyric form, writing subjective, personal poems with universal overarching themes. In that vein, thematic content doesn't necessarily provide the primary sense of cohesion in this collection. Instead, an adherence to lyrical style, a loyalty to the free verse tradition, and the emotional nature of the poems themselves unify the collection as a whole. In the lyric tradition, they often serve as a response to or reflection of a specific occasion or experience, sometimes with a direct, conversational tone, and other times in a loftier, more emotional sense. Thematically, however, the poems in "Celestial Bodies" occasionally deal with the speaker's rumination on a loss or unmet desire. The object of the speaker's affection or anger can be interpreted as various people--lover, father, mother, God--and sometimes the line between one poem and another (in terms of addressee) is intentionally unclear. In addition, the yearning poems are often offset by those communicating indifference, irreverence, or ennui. The speaker, though not usually a direct manifestation of myself, is occasionally informed by my own hang-ups, emotions, or experiences, though many are vicarious. In terms of form, my poems typically veer away from the contemporary experimental lyric and more toward grounded language and concepts. Current experimental poetic trends have only informed the way I write in the sense that I am aware of them. I've delved into reading some of it, and occasionally I'll bear those trends in mind when I'm writing my own words and seeking to expand my perceptions and descriptions. However, my aesthetic choices do not intentionally conform to specific period practices. In terms of personal influence, writers such as Shara McCallum, Keetje Kuipers, Natasha Trethewey, Alicia Ostriker, Anthony Abbott, Terrance Hayes, Anna Journey, and Li-Young Lee, among others, have strongly informed the way I write, sometimes thematically and sometimes in form. While Trethewey writes poems that often adhere to traditional forms, the poems' content--especially that which relates to etiquette and the female body--provides a solid backdrop for my own like-minded messages. Meanwhile, the work of Kuipers and Abbott exists within a pervading sense of loss while relying on natural surroundings and images. Journey's sexual thematic content and Hayes's conversational sense of irreverence and ennui ring true in some of my own poems. While some of these authors do veer into narrative poetry, they also successfully communicate on a lyric level, and much of my work parallels that which they thematically expose and dissect. Many of the poems within this collection are based not on story alone, but on emotion and the speaker's personal struggle with various attitudes and challenges. As a result, the lyric seems appropriate for capturing these emotion-based snapshots and communicating them most effectively to the reader. As Sappho illustrated with her brief, passion-infused poems, a solid narrative structure isn't always necessary for a successful poem; however, the larger context of a collection as a whole can instead serve as the foundation. "Celestial Bodies" operates in the same spirit. "Although they are only breath, words which I command are immortal" -Sappho
Keywords: Literature; Lyric poetry